"I Am Working-Class": Subjective Self-Definition as a Missing Measure of Social Class and Socioeconomic Status in Higher Education Research. (May 2014) - Rubin, Mark; Denson, Nida; Kilpatrick, Sue; Matthews, Kelly E.; Stehlik, Tom; Zyngier, David
This review provides a critical appraisal of the measurement of students' social class and socioeconomic status (SES) in the context of widening higher education participation. Most assessments of social class and SES in higher education have focused on objective measurements based on the income, occupation, and education of students' parents, and they have tended to overlook diversity among students based on factors such as age, ethnicity, indigeneity, and rurality. However, recent research in psychology and sociology has stressed the more subjective and intersectional nature of social class. The authors argue that it is important to consider subjective self-definitions of social class and SES alongside more traditional objective measures. The implications of this dual measurement approach for higher education research are discussed.